Identifying Indigenous Elements in Urban Planning and Architecture of Sapa - Nguyen, Viet Huy; Vu, Thi Huong Lan; Nguyen, Quoc Thong (International Journal of Sustainable Construction Engineering and Technology, 2024)
Since the French started occupying Indochina, there was a demand emerged to build resorts in regions with climatic conditions similar to those in France. The high mountainous areas in Vietnam, especially Sapa, with the favorable climate and natural characteristics, became a focal point for French attention.Since the Doi Moi period, Vietnam has undergone profound changes driven by industrialization and modernization, with notable progress in the tourism industry. In tourist cities like Sapa, these developments have led to significant transformations in both quality and scale. The rapid growth of tourism has revitalized the city, marked by the construction of new architectural systems and the revival of economic, social, and cultural dynamics. However, this expansion has also had substantial impacts on the environment, cultural heritage, societal structures, and landscape architecture of the region.Understanding and analyzing indigenous factors in Sapa's urban planning and architecture provide a critical foundation for evaluating these changes. This approach can guide the formulation of sustainable development strategies that enhance the area's natural and cultural assets while preserving its rich traditions and identity.The study begins with an exploration of the research site, followed by an examination of the local context. By integrating theoretical frameworks with empirical research, the findings identify the distinctive elements of Sapa's urban fabric, offering a foundation for further studies and informed development planning.